Co-use of tobacco and marijuana among young people experiencing homelessness in Los Angeles County. (1st February 2020) - Tucker, Joan S.; Shadel, William G.; Seelam, Rachana; Golinelli, Daniela; Siconolfi, Daniel
Highlights: Most young tobacco users experiencing homelessness also use marijuana. Co-administration is more common than using the products separately or tobacco only. Co-administrators report more cigarette and marijuana use and poorer functioning. Co-administration is associated with exposure to peers who engage in this behavior. Correlates also include perceived health risk (but not cost) vis-à-vis cigarettes. Abstract: Introduction: Tobacco and marijuana co-use among young people in the U.S. is a public health concern that deserves greater attention. This study addresses a significant gap in the literature by examining the prevalence and correlates of tobacco and marijuana co-use among young people experiencing homelessness. Methods: The analytic sample consisted of 449 unaccompanied homeless youth (mean age = 22; 72% male) who had used any type of tobacco product in the past 30 days. Participants were recruited from 12 service sites and 13 street sites in Los Angeles County. Results: Over 90% of young homeless tobacco users reported past month marijuana and tobacco co-use: 65% reported any co-administration (mixing both substances in a cigarette, joint, blunt, bong, hookah, pipe or bowl) and 27% reported only using them separately. Analysis of covariance tests found that co-administrators reported greater quantity and frequency of tobacco cigarette use, more frequent marijuana use and, in some cases, poorer functioning and more severe homelessness compared to other tobacco users (p < 0.05). Logistic regression analysis indicated that co-administration was less likely among youth who were Black (vs. white) and who perceived it as being the same or more harmful than cigarette smoking, but more likely among youth who reported greater exposure to peers who engaged in co-administration (p < 0.05). Conclusions: Co-administration of tobacco and marijuana is prevalent among young tobacco users experiencing homelessness. Results add to a growing literature on the prevalence and potential risks of co-administration among young people that can inform policies aimed at regulating tobacco and marijuana products.